The matching book embedding under some graph operations - Zeling Shao; Min Yao; Zhiguo Li (GTA Research Group, Univ. Newcastle, Indonesian Combinatorics Society and ITB, 2026)
The matching book embedding of a graph G is an embedding of G with the vertices on the spine, and each edge within a single page so that the edges on each page do not intersect and the degree of vertices on each page is at most one. The matching book thickness of G is the minimum number of pages in a matching book embedding of G, denoted by mbt(G). In this paper, the exact matching book thickness of the corona product between a dispersible or nearly dispersible graph and a simple graph is determined. Additionally, the dispersibility of the edge product of a cycle and a simple graph is obtained. Finally the matching book thickness of the comb product of two dispersible graphs is obtained.